Pest management: Reconciling farming practices and natural regulations. (January 2019) - Brévault, Thierry; Clouvel, Pascal
Abstract: Stimulation of ecological processes of natural pest regulation is a promising avenue for inventing new crop protection models, and reducing the dependence of agricultural systems on pesticides. Here, we review and discuss this emerging approach for the development of agroecological management of insect pests, and necessary bridges between agronomy, ecology, and social sciences. Ecological regulation can be harnessed through better knowledge of the life system of pest populations, interactions with trophic resources and natural enemies in agroecosystems, and incorporation of both cultivated and uncultivated habitats in the landscape as the framework to analyse ecological processes. Harnessing these regulation processes also entails taking into consideration the perception of local stakeholders in a participative approach to collective management of resources and innovation processes. The approach that we propose for improved management of crop pests consists in reconciling (i) action on the environment through biodiversity-friendly farming practices and technical innovations, and (ii) action on the landscape to stimulate the ecological processes involved in natural pest regulation. This approach entails a fundamental shift in the contours of action, from a conventional, often individual and independent approach of systematic or symptomatic interventions at a field scale, to collective organisation and management of ecosystem services at a territory scale, also including ecological, economic and social dimensions. Highlights: Stimulation of natural pest regulation is a relevant way for sustainable crop protection. This entails suitable management of functional biodiversity at the landscape scale. Better knowledge of the life system of pest populations in agroecosystems is needed. Participative approach to collective management of resources and innovation is needed.